Immobilized enzyme/microorganism complexes for degradation of microplastics: A review of recent advances, feasibility and future prospects - Tang, K.H.D. (Elsevier B.V., 2022)
Environmental prevalence of microplastics has prompted the development of novel methods for their removal, one of which involves immobilization of microplastics-degrading enzymes. Various materials including nanomaterials have been studied for this purpose but there is currently a lack of review to present these studies in an organized manner to highlight the advances and feasibility. This article reviewed more than 100 peer-reviewed scholarly papers to elucidate the latest advances in the novel application of immobilized enzyme/microorganism complexes for microplastics degradation, its feasibility and future prospects. This review shows that metal nanoparticle-enzyme complexes improve biodegradation of microplastics in most studies through creating photogenerated radicals to facilitate polymer oxidation, accelerating growth of bacterial consortia for biodegradation, anchoring enzymes and improving their stability, and absorbing water for hydrolysis. In a study, the antimicrobial property of nanoparticles retarded the growth of microorganisms, hence biodegradation. Carbon particle-enzyme complexes enable enzymes to be immobilized on carbon-based support or matrix through covalent bonding, adsorption, entrapment, encapsulation, and a combination of the mechanisms, facilitated by formation of cross-links between enzymes. These complexes were shown to improve microplastics-degrading efficiency and recyclability of enzymes. Other emerging nanoparticles and/or enzymatic technologies are fusion of enzymes with hydrophobins, polymer binding module, peptide and novel nanoparticles. Nonetheless, the enzymes in the complexes present a limiting factor due to limited understanding of the degradation mechanisms. Besides, there is a lack of studies on the degradation of polypropylene and polyvinyl chloride. Genetic bioengineering and metagenomics could provide breakthrough in this area. This review highlights the optimism of using immobilized enzymes/microorganisms to increase the efficiency of microplastics degradation but optimization of enzymatic or microbial activities and synthesis of immobilized enzymes/microorganisms are crucial to overcome the barriers to their wide application. Â© 2022 Elsevier B.V.